2018
DOI: 10.15171/jlms.2018.42
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic Lithotripsy Versus Laser Lithotripsy for Ureteral Stones

Abstract: versus laser lithotripsy for ureteral stones. AbstractIntroduction: Several different modalities are available for ureteral stone fragmentation. From them pneumatic and holmium: yttrium-aluminum-garnet (Ho: YAG) lithotripsy have supportive outcomes. In this study we studied 250 subjects who had ureteroscopic pneumatic lithotripsy (PL) or laser lithotripsy (LL). Methods: Two-hundred fifty patients with ureteral stones underwent ureteroscopic lithotripsy (115 subjects in the PL group, 135 subjects in the LL grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 19 publications
9
30
0
Order By: Relevance
“…22 Recently Abedi et al declared that slightly higher stonefree rate was found in the LL group compared to PL group in treating ureteral stones. 23 However, we found that there were no major complications between the 2 groups with no statistical significance.…”
Section: Discussionmentioning
confidence: 62%
“…22 Recently Abedi et al declared that slightly higher stonefree rate was found in the LL group compared to PL group in treating ureteral stones. 23 However, we found that there were no major complications between the 2 groups with no statistical significance.…”
Section: Discussionmentioning
confidence: 62%
“…Transurethral lithotripsy can be done by pneumatic, ultrasonic and laser lithotripter. 20 We noted that the duration of surgery was reasonably short in retrograde assisted PCCL. Therefore, the risk of anesthesia and volume absorption would decrease consequently.…”
Section: Discussionmentioning
confidence: 88%
“…However, endoscopic techniques are performed more commonly than urethroplasty. 12 Today, Ho: YAG lasers broadly used in urological surgery include urolithiasis, [13][14][15] benign prostatic hyperplasia, 16 urinary tract strictures, 17 bladder malignancies or lesions of the external genitalia. 10,18 IU is a kind of transurethral intervention in which the stricture is incised by cold-knife or thermal energy incision.…”
Section: Discussionmentioning
confidence: 99%